Mark Watney’s optimism in Andy Weir’s The Martian - Rahmi Munfangati; Rifdah Diniatulhaq (Universitas Ahmad Dahlan)
The aims of this study are to analyze and identify; (1) Mark Watney’s optimism in the novel and (2) the impact of being optimistic as reflected in the novel. This study belongs to library research. To analyze the data, this study applies a psychological approach. The analyzed data are described by using the descriptive qualitative method, then. After analyzing the novel, it is found that; first, Mark Watney as the protagonist character is an optimist person proved by his goals and expectancy. Based on the types of optimism, Mark’s optimism refers to the comparative optimism and situational optimism. Second, the impact of being optimistic for Mark Watney are; he has high self-efficacy and hopes that somehow leads him to find a way to communicate with people on Earth, growing food and eventually manages to find his way back to the earth.